ANALISIS PERKEMBANGAN ARTIFICIAL INTELLIGENCE DALAM DIAGNOSIS PENYAKIT SERTA DAMPAKNYA TERHADAP PELAYANAN KESEHATAN DI ERA MODERN - Kennan Hamilton (CV. Denasya Smart Publisher, 2026)
The rapid advancement of Artificial Intelligence (AI) technology has significantly impacted various aspects of human life, including the healthcare sector. One of the most prominent applications of AI is its use in disease diagnosis processes. AI's ability to process large volumes of medical data enables healthcare professionals to detect diseases more quickly, accurately, and efficiently. This study aims to analyze the development of Artificial Intelligence in disease diagnosis, identify its role in healthcare services, and examine the impacts and challenges arising from its implementation. The research employs a qualitative approach through a literature review method. Data were collected from scientific journals, research articles, books, and other credible academic sources related to AI applications in healthcare. The findings indicate that AI has substantial potential to improve disease diagnosis through medical image analysis, electronic health record processing, and clinical decision support systems. although AI offers numerous benefits, including improved diagnostic accuracy and healthcare efficiency, it also presents challenges related to patient data privacy, ethical concerns, and technological dependency. Therefore, responsible technological development and clear regulations are essential to ensure that AI implementation in healthcare provides optimal benefits for society.